Review of two-dimensional materials for photocatalytic water splitting from a theoretical perspective - Li, Yunguo; Li, Yan-Ling; Sa, Baisheng; Ahuja, Rajeev (Catalysis science & technology, 2017)
Two-dimensional (2D) materials have shown extraordinary performances as photocatalysts compared to their bulk counterparts. Simulations have made a great contribution to the deep understanding and design of novel 2D photocatalysts. Ab initio simulations based on density functional theory (DFT) not only show efficiency and reliability in new structure searching, but also can provide a reliable, efficient, and economic way for screening the photocatalytic property space. In this review, we summarize the recent developments in the field of water splitting using 2D materials from a theoretical perspective. We address that DFT-based simulations can fast screen the potential spaces of photocatalytic properties with the accuracy comparable to experiments, by investigating the effects of various physical/chemical perturbations. This, at last, will lead to the enhanced photocatalytic activities of 2D materials, and promote the development of photocatalysis. Two-dimensional (2D) materials have shown extraordinary performances as photocatalysts compared to their bulk counterparts.